2018
DOI: 10.1101/507145
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Progress towards lymphatic filariasis elimination in Ghana from 2000-2016: analysis of microfilaria prevalence data from 430 communities

Abstract: 42 Background 43 Ghana started its national programme to eliminate lymphatic filariasis (LF) in 2000, with mass 44 drug administration (MDA) with ivermectin and albendazole as main strategy. We review the 45 progress towards elimination that was made by 2016 for all endemic districts of Ghana and analyze 46 mf prevalence from sentinel and spot-check sites in endemic districts. 47 48 Methods 49We reviewed district level data on the history of MDA and outcomes of transmission assessment 50 surveys (TAS). We furt… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Furthermore, FGDs with participants in the LF endemic communities revealed that MDA visits by CDDs was not consistent, with some occurring once in a year. In Ghana, MDA usually takes place 1-2 weeks between March and June at different endemic communities [34]. Even then, these programs could be halted for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, FGDs with participants in the LF endemic communities revealed that MDA visits by CDDs was not consistent, with some occurring once in a year. In Ghana, MDA usually takes place 1-2 weeks between March and June at different endemic communities [34]. Even then, these programs could be halted for a number of reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst the present study investigated community members with a wide age range (2-86yrs). There are mixed perceptions on whether conducting a school-based or community-based TAS but other authors have drawn attention on possibility of leaving out non-school attendants some of whom might have not received the drugs (Biritwum et al, 2019). For examples in American Samoa, high prevalence of lariasis was observed in community-based assessment (6.2%) than in school-based survey (0.7%) (Sheel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the earlier reports which suggested termination of drug distribution following 5-6 rounds (WHO, 2011), in fact the exact number of treatments to implement such decision was unclear. For example some endemic countries have implemented up to 14 rounds of MDA (Biritwum et al, 2019). The prematurely termination of drug distribution has in part, contributed to rebounce of infection in some endemic countries (Boyd et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Programme design and delivery for included studies(Continued) CDD: community drug distributor; MDA: mass drug administration; PHC: primary Health Centre. For some studies, further information was provided by a:Biritwum 2019; b: Njomo 2012a; c: NVBDCP 2018; d: Kisoka 2016; e: Oscar 2014. …”
mentioning
confidence: 99%